Cell-Sonar, an Easy and Low-cost Method to Track a Target Protein by Expression Changes of Specific Protein Markers - Sabrina Brockmöller; Lara Molitor; Franz Worek; Simone Rothmiller (Bio-Protocol)
Different research methods aim to clarify the intracellular trafficking of target proteins or unknown pathways. Currently, existing methods are mostly complex and expensive, requiring expert knowledge. Detailed microscopy for protein co-localization detection or omic technologies, which provide holistic network data, are elaborate, mostly complex, and expensive to apply. Our protocol illustrates a method to track a target protein by detecting expression changes of user-selected marker proteins that directly or indirectly interact with the target. Modulation of protein expression indicates interactions between the target and marker protein. Even without co-localization analysis, the results of the protein expression change are the first insights into the target's fate. Moreover, the use of the cell-sonar is straightforward and affordable, and the results are rapidly available. Furthermore, this method could also be used to determine if and how pathways are affected by compounds added to the cells. In conclusion, our method is adaptable to a wide range of proteins, easy to apply, inexpensive, and expandable with substances that affect proteins.